Business networks: development of actors’ strategic guidelines from the analysis of negotiation situations in Portugal - Falcão, Pedro Miguel Ribeiro de Almeida Fontes (2009)
Classifications of JEL Classification System: D74 - Conflict; Conflict Resolution; Alliances. L14 - Transactional Relationships; Contracts and Reputation; Networks.